APLIKASI SEVERE PLASTIC DEFORMATION (SPD) DAN HEAVY COLD ROLLING PADA BAJA TAHAN KARAT AUSTENITIK 316L[The Application of Severe Plastic Deformation (SPD) and Heavy Cold Rolling of Austenitic Stainless Steel 316L] - Mabruri, Efendi (Jurnal Metalurgi, 2012)
THE APPLICATION OF SEVERE PLASTIC DEFORMATION (SPD) AND HEAVY COLD ROLLING OF AUSTENITIC STAINLESS STEEL 316L. The grain refinement down to ultrafine sizes is the efective method for strengthening of austenitic stainless steel. This paper reports the application of severe plastic deformation (SPD) using equal channel angular pressing (ECAP) and the application of heavy cold rolling on the austenitic stainless steel (SS) 316L. The experimental results showed that the mechanical properties of SS 316L can be increased significantly by these two techniques. The single pass-ECAP with 0.65 strain increased tensile strength of SS 316L by 1.6 times, whereas heavy cold rolling with 80% reduction and 1.65 strain increased tensile strength by 2.1 times. The annealing treatment at 750 °C decreased tensile strength of 80 % cold rolled SS 316L down to 1055.14 Mpa, however this value is still much larger compared to that of solution treated ones of 655.53 Mpa.